O direito processual na Gortina do século V a.C.: o juiz e a prova (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2022)
This study deals with the court’s fact-finding powers and the judge’s role for gathering evidence (sua sponte) in Gortyn in fifth century BCE. The Great Code of Gortyn (IC IV 72) distinguishes two ways a judge might decide: he may either ‘give judgment’ (δικάδδεν), or ‘decide on oath’ (ὀμνύντα κρίνεν). However, it never refers to the possibility of the court’s interference regarding the collection of evidence. Some authors believe that in the latter case the judge may search for evidence to decide the case. Others exclude this categorically in both judicial manners of making the decision. We tend to agree with the latter way of thinking, since δικάδδεν and ὀμνύντα κρίνεν are legal commands relating to the final phase of making a decision. The Gortynian judge would have to search the applicable law and would not rely solely on the statements of the parties concerning the substantive contents of law. With respect to the question of fact, the judge was a passive fact-finder, who ruled solely on the evidence presented by the parties. Therefore, the judge did not have an active role in relation to obtaining evidence and fact-finding. However, the judges’ recourse to their personal knowledge cannot be completely rejected in Gortyn. The judge who has personal information on the disputed facts will not be impartial, and, consequently, should only be called as a witness, which perhaps was not the case in Gortyn.